(untitled) (Ius Novum, 2020)
The gloss refers to the problem of the correct and accurate description of the act fulfilling the elements of the criminal offence of traffic incident (Article 177 § 1 or § 2 of the Criminal Code) imputed to the defendant in the conviction (Article 413 § 2(1) of the Criminal Procedure Code). The author, elaborating on the arguments supplied by the Supreme Court, takes a position in support of the admissibility of an equivalent phrasing that defines the ‘violation of safety rules in land traffic’, provided that its semantic value corresponds to the statutory element. The author also notes that in specific cases the description of an act based solely on expressions taken from the statutory language could even make it more difficult to present an accurate picture of the perpetrator’s conduct.